The behaviour of financial ratios for capital intensive and labour intensive enterprises during an upswing and decline phase of the economic cycle - Bloom, Jonathan,1976- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2001.